Natural Disasters and University Enrolment: Evidence from L'Aquila Earthquake - Augusto Cerqua; Giorgio Di Pietro (Institute for the Study of Labor (IZA), 2015)
This paper uses the synthetic control method to look at how the L'Aquila earthquake affected subsequent enrolment at the local university. Such an issue is closely related to the economic consequences caused by this event given the large contribution made by the university to the local economy before the earthquake. The empirical results indicate that the earthquake had no statistically significant effect on first-year enrolment at the University of L'Aquila in the three academic years after the disaster. This natural disaster, however, caused a compositional change in the first-year student population, with a substantial increase in the number of students aged 21 or above. This is likely to have been driven by post-disaster measures adopted in an attempt to mitigate the expected negative effects on enrolment triggered by the earthquake. Finally, the results show also that the effect of the earthquake on enrolment varied by Faculty.
Keywords: A20; H84; C23; 330; university enrolment; natural disaster; synthetic control method